2018
DOI: 10.1161/atvbaha.118.311220
|View full text |Cite
|
Sign up to set email alerts
|

Lp(a) [Lipoprotein(a)]-Related Risk of Heart Failure Is Evident in Whites but Not in Other Racial/Ethnic Groups

Abstract: Objective: Lipoprotein(a) [Lp(a)] levels vary by race/ethnicity and were recently found to be associated with risk of heart failure (HF). We aimed to determine whether Lp(a)-related risk of HF is similar across different races and whether Lp(a) may further be related to HF with reduced (HFrEF) or preserved ejection fraction (HFpEF). Approach and Results: In 6,809 participants of the Multi-Ethnic Study of Atherosclerosis, aged 45–84 years and free of cardiovascular disease (CVD), 308 incident HF events occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 23 publications
(28 reference statements)
4
38
0
Order By: Relevance
“…Ethnic difference in Lp(a) levels have been reported previously, with the highest levels in African Americans [18]. Previous MESA studies have also demonstrated ethnic difference in the association of Lp (a) with risk of carotid plaque progression and heart failure, with the association being significant only in Caucasians, but not in other racial/ ethnic groups [17,18]. In the present study, however, the association of elevated Lp(a) with progression of CAC volume was more prominent in African Americans and Hispanic Americans, than in Caucasian and Chinese Americans.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Ethnic difference in Lp(a) levels have been reported previously, with the highest levels in African Americans [18]. Previous MESA studies have also demonstrated ethnic difference in the association of Lp (a) with risk of carotid plaque progression and heart failure, with the association being significant only in Caucasians, but not in other racial/ ethnic groups [17,18]. In the present study, however, the association of elevated Lp(a) with progression of CAC volume was more prominent in African Americans and Hispanic Americans, than in Caucasian and Chinese Americans.…”
Section: Discussionmentioning
confidence: 68%
“…At baseline, venous blood samples were obtained by certified technicians from each participant after a 12-h fast. Lp(a) mass was measured in serum by Health Diagnostics Laboratory (Richmond, Virginia) using a latex-enhanced turbidimetric immunoassay (Denka Seiken, Tokyo, Japan) as described previously [17,18], which controlled for the heterogeneous sizes of apo(a) [19], with a total imprecision <5%.…”
Section: Measurement Of Lp(a) Levelsmentioning
confidence: 99%
“…Consistent to prior reports, results of our current study also suggest that in ACS patients undergoing PCI, compared to those with low Lp(a), patients with high Lp(a) had a higher unadjusted risk of acute stent thrombosis, which might be due to the less optimal post-PCI TIMIE ow in these ACS populations. As shown in Table 4 [24]. Interestingly and importantly, our current study for the rst time showed that compared to those with low Lp(a), patients with high Lp(a) had higher risk of congestive heart failure even after adjustment for potential covariates.…”
Section: Discussionmentioning
confidence: 51%
“…hypertension and diabetes), poor adherence to antiplatelet medications, and among others. Importantly, prior studies also have shown that increased Lp(a) is associated with a variety of cardiovascular diseases such as CHD and congestive heart failure [24][25][26]. The pathophysiological effects of increased Lp(a) on cardiovascular systems are two folds, that is pro-atherosclerosis and pro-thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Significant race interactions were observed, and Lp(a) was further related to a greater risk of heart failure with preserved ejection fraction in white participants. This was independent of aortic valve disease, although the exact mechanism for these associations remains unclear [63].…”
Section: Cross National Studymentioning
confidence: 94%